2003
DOI: 10.1055/s-2003-42644
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Hepatic Encephalopathy in Acute Liver Failure

Abstract: Hepatic encephalopathy (HE) in acute liver injury signifies a serious prognosis. Brain edema and intracranial hypertension are major causes of death in this syndrome. Comparison of HE in acute liver failure (ALF) with that of cirrhosis allows recognition of important differences and similarities. A key role for ammonia in the pathogenesis of both HE and brain edema is now firmly supported by clinical and experimental data. Additional factors, such as infection, products of the necrotic liver, and synergistic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(14 citation statements)
references
References 103 publications
0
13
0
1
Order By: Relevance
“…Gastrointestinal bleeding, excessive protein intake and constipation increase ammonia due to the higher absorption of nitrogenous compounds from the gut and renal failure or hydroelectrolytic abnormalities, often due to diuretics, provoke increased renal ammonia production or reabsorption. In fact, in the recent years a new view of the pathophysiology of HE takes four organs into account in which the traffic of ammonia may result in increases of this substance in the brain: the liver, the gut, the kidney and the muscle [18]. In cases of HE induced by the intake of benzodiazepines, it is obvious that this compound plays a major causative role.…”
Section: The Pathophysiological Basis Of He Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Gastrointestinal bleeding, excessive protein intake and constipation increase ammonia due to the higher absorption of nitrogenous compounds from the gut and renal failure or hydroelectrolytic abnormalities, often due to diuretics, provoke increased renal ammonia production or reabsorption. In fact, in the recent years a new view of the pathophysiology of HE takes four organs into account in which the traffic of ammonia may result in increases of this substance in the brain: the liver, the gut, the kidney and the muscle [18]. In cases of HE induced by the intake of benzodiazepines, it is obvious that this compound plays a major causative role.…”
Section: The Pathophysiological Basis Of He Therapymentioning
confidence: 99%
“…2) [24]. Since the pathophysiological and clinical value of these therapies are discussed elsewhere, the most important aspect to stress here is the fact that a restrictive protein diet worsens the nutritional status of the patients, does not improve the outcome of HE and can actually lead to an increase in ammonia due to reduction in the muscular removal of this substance [18]. In this connection, a recent study has shown that a normoproteic diet can be safely administered to patients with acute HE (fig.…”
Section: The Pathophysiological Basis Of He Therapymentioning
confidence: 99%
“…This high mortality is in part due to the development of severe brain edema that leads to increased intracranial pressure and brain herniation. Currently, there is no effective treatment for the brain edema in ALF other than emergency liver transplantation (24). …”
Section: Introductionmentioning
confidence: 99%
“…[119] Since severe liver pathology, such as liver failure or hepatitis C infection, is associated with encephalitis and cognitive decline,[209] it is easy to imagine that chronic liver disease induced by aluminum could contribute to impaired ability to recover from brain trauma, even in children and young adults.…”
Section: Aluminum Work Synergistically With Glyphosatementioning
confidence: 99%